ENHANCING ATHLETE PERFORMANCE: FUNCTIONAL FOOD MIX IMPACT - Sindhu PB; Ravindra UR; Basavarajaiah DM (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
A prospective observational study was conducted to assess the impact of a formulated functional food mix on athletes’. According to the market survey, a sports food supplement prepared based on the functional ingredients that it was scientifically tested and proved can be stable for a storage period of 13 months. A total of thirty athletes (n = 30), 80% males with an average age of 24 years, participated for a period of 110 days (dietary intervention). The participants were grouped as experimental and naive (n1 = n2 = 15 athletes). All anthropometric parameters were taken and analyzed. Some of the variables showed slight increases, including the IQR of height (1.74–1.75 m), weight (64.09–65.08 kg), BMI (21.0–21.10 kg/m2), and marginal declines among waist circumference (28.83–28.63 cm), hip circumference (36.90–36.00 cm), and triceps skinfold thickness (8.13–8.09 mm). Biochemically, the functional food mix was found to have significant improvements (p